If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (35x + 10) + -10 = (18x + -6) Reorder the terms: (10 + 35x) + -10 = (18x + -6) Remove parenthesis around (10 + 35x) 10 + 35x + -10 = (18x + -6) Reorder the terms: 10 + -10 + 35x = (18x + -6) Combine like terms: 10 + -10 = 0 0 + 35x = (18x + -6) 35x = (18x + -6) Reorder the terms: 35x = (-6 + 18x) Remove parenthesis around (-6 + 18x) 35x = -6 + 18x Solving 35x = -6 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 35x + -18x = -6 + 18x + -18x Combine like terms: 35x + -18x = 17x 17x = -6 + 18x + -18x Combine like terms: 18x + -18x = 0 17x = -6 + 0 17x = -6 Divide each side by '17'. x = -0.3529411765 Simplifying x = -0.3529411765
| 5p+6q-4r+2p-3q+7r-3p= | | 17+5x=-6 | | (5r^2-2r-7)+(r^2-6r+3)= | | m^3+8=0 | | -72y+54+4y=3 | | z^2-11z+24= | | 1/6w=16 | | 80m^3=5m | | 7/10t=392 | | 2xy^3+3x^2y^2z+4=3x^2y+x^3yz+5z | | 528=x*(x+2) | | a=(a^2)/(3) | | 4n-12=7 | | 2xy^3+3x^2y^2z+4= | | lnx+5=12 | | 4y-3=11y+46 | | 6a^2-16a=0 | | 2-5i(4-i)-(2-i)(2+i)= | | 56s^2+17sa-3a^2=0 | | 15x-(4x-3)=91 | | 2+0.25z= | | 3x-4(2-3x)=(x-4)-15 | | 4x+7=8x-12 | | 7*4p-5*3r+3*3q-5*5r+4*5p-10q= | | 2/3=1/3q | | (7+i)-(8-i)= | | 21-4x=-31 | | (9y)/(3y) | | a/b=-8 | | 21/21b=72/21 | | -2x-7(8-5x)-4=x-2+3x | | 5a+8= |